Juridic Analysis Of The Overlapping Ground Problem Resulting From The Difference In Measurement (Research Study For A Free Trade Company And Batam Free Port) - Fadhilah Muhamad Noor; Darwis Anatami; Dahlan Dahlan; Erniyanti Erniyanti; Soerya Respationo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
The earth is the most susceptible object to the issue, the many issues taking place today are due to the varying issues of society, one of which is the overlapping (overlapping) of the land as to the possession of the land floor. The study was done with the purpose of learning about the overlapping land disputes (overlapping) and the encountered obstacles and solutions in the offices of the free trade and Batam free port bodies. The study employs a sociological juxtapoc approach, the is approaches through current legal research, and links with existing facts in society, with analytical research specifications, as to the issues encountered in overlapping (overlapping) lands in the offices of the free trade and Batam free port bodies. In this study, the authors used primary types of data through interviews and field observations supported by secondary data of qualitative library studies. The study indicated that the settlement of land rights issues by mediating in the Office of the Free Trade Company and Batam Free Port had been consistent with the provision of a settlement of the problem carried out by the Office of the Free Trade and the Batam free port. As for the problem at hand, it is the absence of the parties involved and the good faith of the parties involved. As to overlapping (overlapping) ground (overlapping) as a result of loss of land/patent or a measurable system difference, the management of the free trade area and the Batam free port provided the problem with a revised image setting (PL) or a ground reduction reduction with a compulsory annual return on ground space (UWT).